The Influence of New E-PLKK Service Quality, Trust, Consumer Attitude on Customer Satisfaction through Customer Experience and Customer Engagement at the Gresik Branch of BPJS Ketenagakerjaan - Wahyuni, Ratna Dwi; Cempena, Ida Bagus; Budiarti, Endah (International Journal of Economics (IJEC), 2025)
This study investigates the relationships between several key variables. The central questions are: 1) Does the New E-PLKK Service (X₁) impact Customer Satisfaction (Y)? 2) Does it affect Customer Experience (Z)? 3) How does Trust (X₂) influence Customer Satisfaction (Y)? 4) What is its effect on Customer Experience (Z)? 5) Does Customer Behavior (X₃) affect Customer Satisfaction (Y)? 6) How does it influence Customer Experience (Z)? 7) Is there a relationship between Customer Experience (Z) and Customer Satisfaction (Y)? 8) Can Customer Engagement (M) moderate the relationship between Customer Experience (Z) and Customer Satisfaction (Y)? Employing a quantitative approach, this explanatory study systematically addresses these questions. It begins with defining the research background, problem formulation, objectives, limitations, and potential benefits. The methodology includes a literature review, population determination, sample selection, and instrument development. The study surveyed 70 PICs from PLKK across Gresik Regency, utilizing both primary and secondary data sources. Data collection was carried out through questionnaires, and the analysis employed Structural Equation Modeling (SEM). Descriptive analysis summarized the data, while Partial Least Square (PLS) techniques examined latent variables and their interrelations. The findings reveal that the New E-PLKK Service Quality significantly influences Customer Satisfaction but not Customer Experience. Trust positively affects both Customer Satisfaction and Customer Experience. Additionally, Customer Behavior impacts both Satisfaction and Experience, while Customer Experience is shown to influence Satisfaction. However, Customer Engagement does not moderate the effect of Customer Experience on Satisfaction.